Analysis of Implementation of PMK 96/2023: Electronic Data Integration Obligations Between Platforms Trading Through Electronic Systems (PPMSE) And Directorate General of Customs and Excise on Transactions Above 1000 Shipments - Susan Frisca; Andreas Eno Tirtakusuma (Jurnal Smart Hukum (JSH), 2025)
This study analyzes the implementation of Minister of Finance Regulation No. 96/PMK.04/2023 which mandates electronic data integration between Electronic System Trading Platforms (PPMSE) and the Directorate General of Customs and Excise for transactions exceeding 1000 shipments. Using a quantitative approach with explanatory and evaluative design, the research involved 178 PPMSE platforms and 87 DJBC officials as respondents. Results show implementation success rate of 89.6% with compliance rate improvement from 64.7% to 92.4%. The 1000-shipment threshold proved highly effective with 94.3% coverage ratio of total cross-border e-commerce transaction value. Implementation generated state revenue increase of IDR 5,198.8 billion (65.1%) with benefit-cost ratio of 14.17:1. Operational efficiency improved significantly through clearance processing time reduction from 72.4 hours to 18.6 hours and 89.8% officer productivity increase. Enforcement mechanisms demonstrated high effectiveness with 97.7% case resolution rate and 93.8% post-sanction compliance. The system built has scalability up to 300% transaction volume and has become regional best practice. PMK 96/2023 successfully created sustainable digital taxation transformation with positive impacts on transparency, efficiency, and competitiveness of Indonesia's e-commerce ecosystem.